Magnesium ions alleviate the negative effect of manganese on Glomus claroideum BEG23 - Malcová, R; Gryndler, M; Vosátka, M (Mycorrhiza, 2002)
The phytotoxicity of excessive levels of manganese (Mn), an essential micronutrient, can be alleviated significantly by a high supply of magnesium (Mg) ions to plants. A similar interaction of these two elements in the development of arbuscular mycorrhizal (AM) fungi has been verified in two experimental systems. In in vitro experiments, an outgrowth of hyphae from excised, surface-disinfected root segments colonised with Glomus claroideum BEG23 was measured after 5 days incubation in liquid media. When only Mn ions were present in the media at higher concentrations (>0.05 mM), the growth of hyphae from root segments was reduced significantly. Addition of magnesium sulphate to the incubation solution reduced the inhibitory effects of Mn on hyphal growth. Alleviation of Mn toxicity by Mg ions observed in in vitro experiments was verified also for the symbiotic association between G. claroideum and maize as a host plant in a hydroponics sand culture experiment.
Keywords: Symbiosis; Zea mays; hydroponie; kultivační média; houby; Mycorrhizae; Hyphae; kukuřice setá; hyfy; mangan; Manganese; mykorhiza; hořčík; symbióza; Fungi; Hydroponics; Magnesium; Culture Media